Toksikološki vidiki izpostavitve bisfenolom v termičnem papirju - Franko, Nina (Farmacevtski vestnik, 2024)
The use of bisphenol A in plastics and thermal paper is being increasingly tightened by regulatory authori¬ties worldwide, as it is a confirmed endocrine di¬sruptor and affects the pathogenesis of a number of diseases. As a result, the industry is replacing it with substitutes that are not sufficiently regulated for safety. There are too few toxicological studies to confirm that they are safer than bisphenol A. However, due to the widespread use of bisphenol A and its substi¬tutes, they are found in the environment and in living organisms. Bisphenols are also present in thermal paper used for cash receipts and labels for food and biological samples in medical laboratories. After con¬tact, they are absorbed into the body through the skin and enter the systemic circulation in non-meta-bolised form. In this review article, we have compiled information on the occurrence of bisphenols in ther¬mal paper, their capacity for transdermal entry into the body and the potential health risks.
Keywords: bisfenol A; Hormonski motilci; motilci endokrinega sistema; nadomestki; termični papir; toksični učinki; Toksičnost